Periodic solutions of nonlinear differential equations with pulse influence in a Banach space - Perestyuk, N.A.; Slyusarchuk, V.E. (Український математичний журнал, 1995)
Rank conditions for control of linear pulse systems are established. An example of control synthesis in a problem for linear pulse systems is given.